2017
DOI: 10.1016/j.limno.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of land use at different spatial scales on instream features in agricultural streams

Abstract: The conversion of forests into agriculture has been identified as a key process for stream homogenization. However, the effects of this conversion can be scale-dependent. In this context, our aim was to identify the influence of different land uses at different spatial scales (catchment, drainage network and local) on instream features in agricultural streams. We defined six classes of land use: native forest, reforestation, herbaceous and shrubs, pasture, sugarcane and other categories. We obtained 22 variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 45 publications
4
19
0
3
Order By: Relevance
“…We quantified land cover variables for the entire drainage network upstream of the sampling site (hereafter "total catchment") and within a 30-m buffer extending 300 m upstream and downstream from the sampling site (hereafter "immediate catchment"; see Supporting Information Figure S1) to capture potential landscape influences on stream fish assemblages (Frimpong et al, 2005;Molina, Roa-Fuentes, . Buffer zones at the immediate catchment scale are comparable to the way riparian buffers are measured according to Brazilian law.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…We quantified land cover variables for the entire drainage network upstream of the sampling site (hereafter "total catchment") and within a 30-m buffer extending 300 m upstream and downstream from the sampling site (hereafter "immediate catchment"; see Supporting Information Figure S1) to capture potential landscape influences on stream fish assemblages (Frimpong et al, 2005;Molina, Roa-Fuentes, . Buffer zones at the immediate catchment scale are comparable to the way riparian buffers are measured according to Brazilian law.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…Changes in stream habitat caused by deforestation have been observed in several studies (Allan & Castillo, ; Leitão et al, ; Molina et al, ; Scott & Helfman, ), but most of these studies were developed at smaller scales and without a biogeographical comparative approach, such as the one applied in this study. Native forest plays a vital role in physical channel heterogeneity by supplying large wood, branches, litter and roots to aquatic systems (Allan, ; Jackson et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Forested riparian zones could feasibly buffer stream habitats to changes in drainage basin land use (and thus cause a lack of relationship between instream and drainage basin attributes), but almost all of the study sites lacked intact riparian forest. Furthermore, a recent study from the same region (Molina et al, 2017) found that forested riparian zones had no effect on instream habitat and suggested that riparian zones were not sufficient to buffer streams from changes in land use in the drainage basin. That being said, we detected evidence of a time lag or legacy effect, thus the effects of rapid conversion of the landscape for biofuel production on instream habitat and biodiversity are presumably not yet fully evident.…”
Section: Magnitude Of Change In Drainage Basin Land Use Was Not Corrementioning
confidence: 99%
“…Cumulative land-use changes for the study area over the past century result in less than 4% of native forest remaining in small and isolated fragments (Nalon, Mattos, & Franco, 2008). Moreover, streams from this area have insignificant amount of riparian forest, because most of the area has been used by livestock grazing (Molina, Roa-Fuentes, Zeni, & Casatti, 2017). Consequently, most of the streams show high physical degradation and relatively homogenous fish assemblages (Casatti et al, 2006(Casatti et al, , 2015.…”
Section: Study Areamentioning
confidence: 99%